Costs of hospitalization in preterm infants: impact of antenatal steroid therapy - Joice Fabiola Meneguel Ogata; Marcelo Cunio Machado Fonseca; Milton Harumi Miyoshi; Maria Fernanda Branco de Almeida; Ruth Guinsburg (Elsevier, 2016)
Objective: To estimate the costs of hospitalization in premature infants exposed or not to antenatal corticosteroids (ACS). Method: Retrospective cohort analysis of premature infants with gestational age of 26-32 weeks without congenital malformations, born between January of 2006 and December of 2009 in a tertiary, public university hospital. Maternal and neonatal demographic data, neonatal morbidities, and hospital inpatient services during the hospitalization were collected. The costs were analyzed using the microcosting technique. Results: Of 220 patients that met the inclusion criteria, 211 (96%) charts were reviewed: 170 newborns received at least one dose of antenatal corticosteroid and 41 did not receive the antenatal medication. There was a 14-37% reduction of the different cost components in infants exposed to ACS when the entire population was analyzed, without statistical significance. Regarding premature infants who were discharged alive, there was a 24-47% reduction of the components of the hospital services costs for the ACS group, with a significant decrease in the length of stay in the neonatal intensive care unit (NICU). In very-low birth weight infants, considering only the survivors, ACS promoted a 30-50% reduction of all elements of the costs, with a 36% decrease in the total cost (p = 0.008). The survivors with gestational age <30 weeks showed a decrease in the total cost of 38% (p = 0.008) and a 49% reduction of NICU length of stay (p = 0.011). Conclusion: ACS reduces the costs of hospitalization of premature infants who are discharged alive, especially those with very low birth weight and <30 weeks of gestational age. Resumo: Objetivo: Estimar os custos da internação hospitalar de prematuros, cujas mães receberam ou não corticoide antenatal (CEA). Método: Coorte retrospectiva de prematuros sem malformações congênitas com idade gestacional de 26 a 32 semanas, nascidos entre janeiro/2006 e dezembro/2009, em hospital público, terciário e universitário brasileiro. Coletaram-se dados demográficos maternos e dos recém-nascidos (RN), a morbidade neonatal e utilização de recursos de saúde durante a internação hospitalar. Os custos foram analisados pela técnica de microcosting. Resultados: Dos 220 nascidos que obedeciam a critérios de inclusão, 211 (96%) prontuários foram revisados: 170 receberam CEA e 41 não receberam a medicação. Analisando-se toda a população, houve redução de 14-37% entre os diferentes componentes do custo nos pacientes expostos ao CEA, sem significância estatística. Na análise de prematuros que receberam alta hospitalar vivos, o grupo com CEA teve redução de 24-47% nos vários componentes dos custos hospitalares, com diminuição significante dos dias de internação em terapia intensiva. Os nascidos com peso <1500 g, considerando-se somente os sobreviventes, são aqueles que mais se beneficiaram da administração do CEA, com redução significante de todos componentes dos custos em 30-50%, sendo tal diminuição de 36% no custo total (p = 0,008). Para o grupo com idade gestacional <30 semanas, também sobreviventes, houve diminuição do custo total de 38% (p = 0,008) e redução de 49% dos dias de internação em UTI neonatal (p = 0,011). Conclusões: O CEA reduz o custo hospitalar de prematuros que sobrevivem à internação após o parto, principalmente naqueles abaixo de 1500 g e 30 semanas de idade gestacional. Keywords: Preterm infant, Costs and cost analysis, Hospitalization, Glucocorticoids, Palavras-chave: Prematuro, Custos e análise de custos, Hospitalização, Glucocorticoides